Effects of a psychosocial intervention on the quality of life or primary caregivers of women with breast cancer in Abuja, Nigeria - Gabriel, Israel Olatunji (Division of Nursing and Midwifery, 2018)
Studies have shown that limited attention has been paid to the psychosocial wellbeing of caregivers of patients undergoing care and treatment for breast cancer in Nigeria. There are no interventions in place to cater for their needs despite, the psychological problems faced by this group of people. This study investigated the effectiveness of a psychosocial intervention in term of impact on the quality of life (QOL) of primary caregivers of women with breast cancer in Abuja, Nigeria. Using a quasiexperimental design, sample of 108 participants assigned to the intervention and control groups, the study made use of the Zarit Burden Interview (ZBI) and Caregiver Quality of Life Index-Cancer (CQOLC) to measure caregiver burden and QOL respectively. The hypothesis for the study was that the primary caregivers of women with breast cancer who receive a psychosocial intervention programme will report improved QOL compared with caregivers who do not attend a psychosocial intervention programme. The study established that there were a negative linear relationship between caregiver burden and QOL (R = -0.45, p < 0.001) as a basis for intervention, and also that 29% variance of QOL could be explained by caregiver burden. The intervention results showed that at baseline 51.9% participants reported moderate to severe burden and 48.1% reported severe burden. These figures reduced to 22.3% and 12.6% for moderate to severe and severe burden respectively at 6 weeks after intervention, and further reduced to 18.6% and 4.9% respectively at 12 weeks after intervention. Comparing the QOL of the intervention and control groups, the results showed a significant difference on the score at baseline, 6 and 12 weeks. However, looking at performance of the intervention group, there was no significant different at baseline and 6 weeks (t=0.83, p < 0.05), and baseline and 12 weeks (t=1.65, p < 0.05). With reference to the caregiver burden of the intervention and control groups, it was found that a significant difference existed at baseline (t=9.33, p < 0.001). In respect of the impact of the intervention on caregiver burden of the intervention group, results showed a significant difference between baseline and 6 weeks (t=30.34, p < 0.001) and between baseline and 12 weeks (t = 36.80, p < 0.001) after intervention. The study concluded that the psycho-education intervention significantly affected caregiver burden but did not affect caregivers' QOL. Therefore, there is a need for a psycho-education intervention for caregivers of patients with breast cancer, in order to reduce the burden and help them cope with the work of caregiving. Appropriate supportive interventions should be made available to support the close family members of patients with breast cancer in order to reduce caregiver burden. Relevant stakeholders in the healthcare sector especially in palliative care should promote awareness of carer needs. The provision of intervention programmes for caregivers requires further research to develop contextually specific programmes and services which will improve the QOL of caregivers.